Traditional domestic interiors in the pre-colonial, colonial and post-colonial periods: the Nigerian case - Ayuba, Philip; Kolo, Salome; Alemede, Daniel (Penerbit Universiti Kebangsaan Malaysia, 2020)
The culture of a people is defined by their social environment, which leads to different needs and wants, and the interpretation of these requirements. This paper discusses the domestic interior scene in Nigeria during the pre-colonial, colonial and postcolonial eras, taking Hausa, Igbo and Yoruba cultures as cases, which reflect the country’s diversity. There are several studies carried out by researchers in the field of interior design. However, the study of the Nigerian interior is an area not widely covered; thus, this paper examines the traditional interior design practices in order to establish the influences of the domestic interior and highlight important aspects of the country’s culture in a bid to preserve its rich heritage which is gradually fading away. The study reveals that traditional architecture is a product of the physical environment and cultural needs in creating a fusion between the traditional interiors and the contemporary.